Pancasila as a Philosophical System: Pancasila as a Solution of Current Issues: Pancasila Sebagai Sistem Filsafat: Pancasila Sebagai Solusi Permasalahan Aktual - Desi Yunita Putri Desi; Arie Ramadhani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This paper examines Pancasila as a philosophical system that provides solutions to current problems. Recently, numerous issues have arisen in Indonesia, such as issues related to ethnicity, religion, race, and intergroup relations (SARA), the high rate of corruption in Indonesia, and the decline in youth morals. The research method used in this research uses a qualitative approach with a literature study method (library research) by collecting sources or information based on secondary sources in the form of literature reviews or secondary sources obtained from books, journal articles, scientific proceedings, and other academic writing. The main focus of this research is to analyze Pancasila as a solution to actual problems based on an in-depth study of Pancasila as a philosophical system. The analysis is carried out by examining actual problems in Indonesia by linking them through a study of the contents and structure of the Pancasila principles within the framework of ontology, epistemology, and axiology. The results obtained are that in resolving all existing problems, it must be returned to Pancasila as the basis of state philosophy, Pancasila must be internalized and implemented in every aspect of life. Pancasila as a philosophical system is essentially a system of knowledge in everyday life. Pancasila is used as a guideline for the Indonesian nation as a basis for humans to solve a problem with an ontological, epistemological and axiological basis